Improved Guideline Adherence and Reduced Brain Dysfunction After a Multicenter Multifaceted Implementation of ICU Delirium Guidelines in 3, 930 Patients. Issue 3 (March 2019) - Trogrlić, Zoran; van der Jagt, Mathieu; Lingsma, Hester; Gommers, Diederik; Ponssen, Huibert H.; Schoonderbeek, Jeannette F. J.; Schreiner, Frodo; Verbrugge, Serge J.; Duran, Servet; Bakker, Jan; Ista, Erwin
Abstract : Objectives: Implementation of delirium guidelines at ICUs is suboptimal. The aim was to evaluate the impact of a tailored multifaceted implementation program of ICU delirium guidelines on processes of care and clinical outcomes and draw lessons regarding guideline implementation. Design: A prospective multicenter, pre-post, intervention study. Setting: ICUs in one university hospital and five community hospitals. Patients: Consecutive medical and surgical critically ill patients were enrolled between April 1, 2012, and February 1, 2015. Interventions: Multifaceted, three-phase (baseline, delirium screening, and guideline) implementation program of delirium guidelines in adult ICUs. Measurements and Main Results: The primary outcome was adherence changes to delirium guidelines recommendations, based on the Pain, Agitation and Delirium guidelines. Secondary outcomes were brain dysfunction (delirium or coma), length of ICU stay, and hospital mortality. A total of 3, 930 patients were included. Improvements after the implementation pertained to delirium screening (from 35% to 96%; p < 0.001), use of benzodiazepines for continuous sedation (from 36% to 17%; p < 0.001), light sedation of ventilated patients (from 55% to 61%; p < 0.001), physiotherapy (from 21% to 48%; p < 0.001), and early mobilization (from 10% to 19%; p < 0.001). Brain dysfunction improved: the mean delirium duration decreased from 5.6 to 3.3 days (–2.2 d; 95% CI, –3.2 to –1.3; p < 0.001), and coma days decreased from 14% to 9% (risk ratio, 0.5; 95% CI, 0.4–0.6; p < 0.001). Other clinical outcome measures, such as length of mechanical ventilation, length of ICU stay, and hospital mortality, did not change. Conclusions: This large pre-post implementation study of delirium-oriented measures based on the 2013 Pain, Agitation, and Delirium guidelines showed improved health professionals' adherence to delirium guidelines and reduced brain dysfunction. Our findings provide empirical support for the differential efficacy of the guideline bundle elements in a real-life setting and provide lessons for optimization of guideline implementation programs. Abstract : Supplemental Digital Content is available in the text.